Evolution of the spin hall magnetoresistance in Cr2O3/Pt bilayers close to the Néel temperature - Schlitz, Richard; Kosub, Tobias; Thomas, Andy; Fabretti, Savio; Nielsch, Kornelius; Makarov, Denys; Goennenwein, Sebastian T. B. (Applied Physics Letters, 2018)
We study the evolution of magnetoresistance with temperature in thin film bilayers consisting of platinum and antiferromagnet Cr2O3 with its easy axis out of the plane. We vary the temperature from 20 °C to 60 °C, in the vicinity of the Néel temperature of Cr2O3 of approximately 37 °C. The magnetoresistive response is recorded during rotations of the external magnetic field in three mutually orthogonal planes. A large magnetoresistance having a symmetry consistent with a positive spin Hall magnetoresistance is observed in the paramagnetic phase of Cr2O3, which however vanishes when cooling to below the Néel temperature. Compared to analogous experiments in a Gd3Ga5O12/Pt bilayer, we conclude that a paramagnetic moment in the insulator induced by an applied magnetic field is not sufficient to explain the observed magnetoresistance. We speculate that the type of magnetic moment at the interface qualitatively impacts the spin angular momentum transfer, with the 3d moments of Cr sinking angular momentum much more efficiently as compared to the more localized 4f moments of Gd.
CRIS-Team Scopus Importer:2022-04-14